Theoretical study to determine the band gap of the bis(benzoylacetone)zirconium complex compound using the PM3 semi-empirical computational method - Muhammad Yusuf (Pascasarjana Universitas Negeri Medan, 2023)
TThe bis(benzoylacetone)zirconium (bis(bzac)2Zr) complex compound has been used as a catalyst in various chemical reactions. The aim of this study was to compare the band gap and maximum wavelength of the bis(bzac)2Zr complex with its ligands. The software used is HyperChem 8.0. Calculations begin by optimizing complex compounds. After that, the HOMO-LUMO energy is calculated so that the band gap is obtained. Meanwhile, the calculation of the maximum wavelength is carried out based on UV calculations by using the singly excited method. The addition of Zr atoms to the ligand is expected to reduce the band gap of the complex. On the other hand, the maximum wavelength of the resulting complex is expected to be higher than that of the ligand. Based on the calculation results, the band gap of the complex compounds is 6.128 eV, while the maximum wavelength produced is 383.54 nm. The band gap of the ligand is larger than that of the complex, which is 9.031 eV, while the maximum wavelength of the ligand is 261.25 nm.Keywords: Bis(benzoylacetone)zirconium; Band gap; Complex; Wavelength